Adverse events in anaesthesia care - Bejvančická, Petra; Brabcová, Iva (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2020)
The goal of this review study was to summarize research conclusions on reported adverse events in anaesthesia care regarding paediatric and adult patients in the last 10 years. Methods: Relevant sources were found in scientific databases EBSCO, PubMed, Science Direct, Wiley and Scopus. We used the following keywords: adverse events/incident/malpractice, anaesthesia, report. Other criteria for the inclusion of studies were: full-text, English language, publications that were no older than 10 years (2009–2019) and human related. In the end, we included 15 studies. Results: The studies (analytical, prospective, retrospective, cohort, observational, systematic revisions and meta-analyses) mostly specify the areas and frequencies of reported adverse events and deal with the efficiency of report procedures and their implementation in clinical practice. The most frequent adverse events that occurred in anaesthesia care were respiration and cardiovascular problems and medical errors. The level of their occurrence varied by the patients’ age. Conclusions: The monitoring and assessment of adverse events is an effective instrument for the improvement of quality and safety in anaesthesia practical care. The main problem is the unwillingness of medical workers to participate in reporting adverse events and the incompatibility of adverse event databases in anaesthesia care.
Keywords: Adverse event; Anaesthesia; Patient safety; Perioperative care; Report